Electronic ongoing assessment system (e-OGA) - Mahadi, Shafaruniza; Ahmad, Shamsatun Nahar; Ishak, Isma (Universiti Teknologi MARA, Kedah, 2023)
Universiti Teknologi MARA (UiTM) developed the current system, known as the e-RESULT Exam System (eRES), for final grades. The system contained both OGA and final exam results. Preparing for the OGA mark is crucial because it must be completed prior to the final exam for students to have sufficient time to study effectively for the final exam. Current practice, lecturers will print the OGA mark from eRES and distribute it to their students via WhatsApp or Telegram group. This way of informing students about their OGA marks is not confidential and cannot be accepted by some students. Consequently, the students develop mental health issues, experience dissatisfaction, and have their minds distorted. Hence e-OGA is designed to address this issue. The e-OGA is a new electronic ongoing assessment mark system for managing student achievement which consists of quizzes, tests, and assignments (individual or group project). It is developed by using MySQL, PHP, and DBLC. The mechanism of the system enables each student to view their own OGA marks privately. By employing this tactic, a student's OGA grade will not be disclosed to their peers. For future projects, e-OGA and eRES will be integrated in such a way that the OGA marks can be imported into eRES. This makes it easier for lecturers to enter only the final exam grades into eRES.